Cytochrome aa3 gene regulation in members of the family Rhizobiaceae: comparison of copper and oxygen effects in Bradyrhizobium japonicum and Rhizobium tropici. - Gabel, C (1994)
Dithionite-reduced minus ferricyanide-oxidized difference spectra on membranes from Rhizobium tropici (formerly Rhizobium leguminosarum bv. phaseoli) incubated at progressively lower O2 concentrations showed only a slight concomitant decrease in A603, the alpha-peak of cytochrome aa3. In contrast to previous results on Bradyrhizobium japonicum, R. tropici showed no significant O2-mediated reduction in the level of either coxA transcription or cytochrome aa3 activity (as measured by ascorbate-N,N,N',N'-tetramethyl-p-phenylenediamine [TMPD] oxidase) even in the cells incubated at 12.5 microM O2. Bean nodule R. tropici bacteroids contained 65% of the fully aerobic free-living levels of the coxA transcript. Primer extension analyses established the transcription initiation site of the R. tropici coxA genes. Sequence analyses of the regions upstream of the transcription initiation site revealed no homology with previously reported Rhizobiaceae family promoters, including the coxA promoter of B. japonicum. The R. tropici deduced CoxA sequence itself is highly homologous to the B. japonicum and Paracoccus denitrificans CoxA sequences. In both B. japonicum and R. tropici, coxA transcript levels were the same for cells grown with copper (0.02 microM) in the medium or in medium completely devoid of copper. However, a posttranscriptional effect of copper deprivation was observed for both bacteria; difference absorption spectra on membranes from cells grown without copper showed that B. japonicum lacked spectroscopically detectable cytochrome aa3, whereas R. tropici retained approximately 50% of normal cytochrome aa3 levels.